MP-V1 from the Venom of Social Wasp Vespula vulgaris Is a de Novo Type of Mastoparan that Displays Superior Antimicrobial Activities - Yangseon Kim; Minky Son; Eun-Young Noh; Soonok Kim; Changmu Kim; Joo-Hong Yeo; Chanin Park; Keun Woo Lee; Woo Young Bang (Molecules, 2016)
Mastoparans from the venom of social wasps have attracted considerable attention as effective antibiotic candidates. In this study, mastoparan V1 (MP-V1) from Vespula vulgaris was first disclosed to have a peptide amino acid sequence distinct from typical mastoparans and its biochemical properties and antimicrobial effects were compared with those of typical mastoparans MP-L, -X(V) and -B. Circular dichroism (CD) spectroscopy revealed that MP-V1 and -X(V) form more stable α-helical conformations in lipid membrane-like environments than MP-L and -B. In parallel, these two also showed more effective antimicrobial activities against the pathogens than did MP-L and -B. Although MP-V1 had a less stable α-helical conformation than MP-X(V), it showed stronger antimicrobial effects against Streptococcus mutans and Salmonella enterica than MP-X(V). In the meantime, analysis of hemolytic activity revealed a range of doses (~50 μM) that exhibited little potent cytotoxicity on human erythrocytes. Finally, the atypical MP-V1 peptide amino acid sequence provided important clues to understanding its antimicrobial mechanism from a structural perspective. Therefore, it has been concluded that MP-V1 is a de novo type of mastoparan with superior antimicrobial activities against both pathogenic bacteria and fungi, which may be useful in developing multipurpose antimicrobial drugs against infectious diseases.